The Signaling Pathway of PGE2 and Its Regulatory Role in T Cell Differentiation - Yang An; Jiameng Yao; Xiaoyin Niu (Hindawi Limited, 2021)
Prostaglandin E2 (PGE2) is a lipid mediator derived from the fatty acid arachidonic acid. As an essential inflammatory factor, PGE2 has a critical impact on immune regulation through the prostanoid E (EP) receptor pathway. T cells, including CD4+ and CD8+ T cell subsets, play crucial roles in the adaptive immune response. Previous studies have shown that PGE2 is involved in regulating CD4+ T cell differentiation and inflammatory cytokine production via the EP receptor pathway, thereby affecting the development of diseases mediated by CD4+ T cells. In this review, we summarize the signaling pathway of PGE2 and describe the relationship between PGE2 and T cell differentiation. Hence, this review may provide important evidence for immune therapies and may even promote the development of biomedicines.